Urgency of Stakeholders in Improving the Quality of Education - Dinil Abrar Sulthani; Ianatut Thoifah (Riwayat: Educational Journal of History and Humanities, 2022)
Interactions between education providers and stakeholders who misperception and miscommunication have a negative impact on the quality of education. This paper aims to provide a complete and comprehensive discussion of the urgency of stakeholders in their roles, functions and understand their rights and obligations. The research method used in this paper is a qualitative method with a library research approach. The results of this study describe the urgency of stakeholders in terms of their role in providing information in the form of questions, inputs, suggestions and criticisms addressed to education providers, and stakeholders prioritizing ethical principles and functions when interacting with the school, as well as education providers updating the rules and formulas that are appropriate for the function and appropriate for the learning process. Formulas or learning formulas that integrate the interaction of the school with stakeholders must be applied massively. The interactions that are built lead to improving the quality of education. The conclusions of this paper lead to three aspects, first, the strategic role of stakeholders, Second, the rules and formulas for the interaction of education providers, and Third, the principles and functions of stakeholder interactions.